Fatty Acids of Some Moss Species from Germany - Pejin, Boris; Vujisic, Ljubodrag; Sabovljevic, Aneta; Sabovljevic, Marko; Tesevic, Vele; Vajs, Vlatka (Asian Journal of Chemistry, 2011)
The fatty acid composition of three mosses collected in Germany was preliminary analyzed by gas chromatography (GC-FID) and gas chromatography-mass spectrometry (GC-MS) for the first time. It was found that Hypnum jutlandicum could be a promising source of elaidic acid (24.36 %) while Bryum moravicum could represent an interesting reservoir of α-linolenic acid (19.55 %).